Menjaga Kesehatan Ginjal dengan Konsep Kesehatan secara Holistik pada Siswa SMAN 1 Giri Banyuwangi - Putri, Novita Surya; Firmanti, Tria Anisa; Andrik Hermanto; Wilujeng, Atik Pramesti; Ali Syahbana (Journal of Health Innovation and Community Services, 2022)
Introduction: Chronic Kidney Disease (CKD) is a non-communicable disease whose prevalence is still high and is still widely found in Indonesia. Chronic kidney disease (CKD) can affect metabolism in the body and disrupt fluid and electrolyte balance. Patients who have chronic kidney disease (CKD) will have an experience dependence on kidney replacement therapies such as hemodialysis, peritoneal dialysis, or kidney transplantation. Prevention of chronic kidney disease by providing knowledge related to the importance of maintaining the kidneys can improve understanding, especially in adolescents. Purpose: Respondents can know and understand the importance of holistically maintaining kidney health. Method: The implementation of community service uses the method of lectures and discussions by providing educational materials to maintain kidney health with the concept of holistic health. Results: Students understand the importance of holistically maintaining kidney health. Conclusion: Providing education related to chronic kidney disease (CKD) is effective to increasing knowledge in the younger generation as a preventive measure of non-communicable diseases, especially chronic kidney disease.